From Agile Systems to Behavioral Health: Leveraging Tech Leadership to Build Scalable Care Models for Children with Autism - Frank Ayokunle Okuwobi,; Opeoluwa Oluwanifemi Akomolafe,; Nkoyo Lynn Majebi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The increasing prevalence of autism spectrum disorder (ASD) among children has created unprecedented demand for specialized behavioral health services, with current diagnostic rates indicating that 1 in 44 children are identified with ASD (Maenner et al., 2023). Traditional care delivery models have proven inadequate to meet this growing need, creating significant access barriers and long waiting lists that delay critical early intervention services. The impact of electronic health records on healthcare delivery and patient outcomes has become increasingly important in addressing these challenges (Enahoro et al., 2024). This comprehensive analysis examines how agile systems thinking and technology leadership principles can be strategically applied to develop scalable, evidence-based care models for children with autism. The integration of agile methodologies, originally developed for software development, offers a transformative framework for addressing the complex, iterative nature of autism care delivery while maintaining quality standards and improving accessibility. This study explores the intersection of technology leadership, systems thinking, and behavioral health intervention, demonstrating how digital transformation strategies can enhance service delivery efficiency without compromising therapeutic outcomes. Through systematic analysis of current care models, technological innovations, and implementation frameworks, this research identifies key opportunities for leveraging agile principles to create responsive, adaptive care systems. The analysis encompasses telehealth integration, data-driven decision making, automated screening processes, and collaborative care coordination platforms that can significantly expand reach while maintaining personalized treatment approaches. The findings reveal that successful implementation of technology-enhanced care models requires careful attention to stakeholder engagement, privacy considerations, cultural competency, and sustainable funding mechanisms. Organizations that successfully integrate agile methodologies with autism care delivery demonstrate improved efficiency metrics, reduced wait times, enhanced family satisfaction, and better therapeutic outcomes. However, implementation challenges include digital equity concerns, clinician training requirements, regulatory compliance, and the need for robust data governance frameworks. This research contributes to the emerging field of digital health transformation in developmental disabilities by providing a comprehensive framework for implementing scalable autism care models. The implications extend beyond individual healthcare organizations to inform policy development, funding priorities, and professional development initiatives. The study concludes that while technology cannot replace the essential human elements of autism care, strategic integration of agile systems and tech leadership principles can significantly enhance accessibility, efficiency, and outcomes for children with autism and their families.
Keywords: autism spectrum disorder; agile methodology; digital health; behavioral health technology; scalable care models; telehealth; children's mental health; healthcare innovation; systems thinking; tech leadership